Evolución de la Tripanosomosis bovina po Trypanosoma vivax en Formosa (Argentina) Años 2007-2012 y su potencial dispersión en el país - Monzon, Carlos Manuel (2013)
Abstract: This paper based on parasitological diagnosis made in cattle, describes the evolution of the T.vivax epizootic wave started in Argentina at the end of 2006 year. Analyzes the frequency of infected animals in different months of the year, in addition to the clinical and epidemiological characteristics of this new disease in cattle in Argentina. Based on the epidemiological history of this tripanosomosis in neighbors countries it warns about the spread of the disease to the most important domestic livestock of Argentina at the Mesopotamia and the Pampa Humeda regions